Superordinate identities and intergroup conflict: the ingroup projection model - Wenzel, M. (2019)
This chapter summarises results from a research programme on the psychological basis of tolerance and discrimination in intergroup relations, with particular consideration of the role of superordinate identities. According to the ingroup projection model, a relevant superordinate group provides dimensions and norms for comparisons between ingroup and outgroup. Groups gain positive value or status when they are considered prototypical for the (positively valued) superordinate group. Group members tend to generalise (project) distinct ingroup characteristics onto the superordinate category, implying the relative prototypicality of their ingroup. To the extent that outgroup difference is regarded as a deviation from the ethnocentrically construed prototype it is evaluated negatively. Our research studied consequences and determinants of ingroup projection, as well as moderators of its implications. The findings contribute to a deeper understanding of the processes involved in intergroup discrimination and indicate new pathways for the reduction of prejudice, towards mutual intergroup appreciation and tolerance.